Out of balance: conflicts of interest persist in food chemicals determined to be generally recognized as safe - Klara Matouskova; Thomas G. Neltner; Maricel V. Maffini (BMC, 2023)
Abstract Manufacturers of chemicals added to food are responsible for determining that the use of their products is safe. There are two major legal definitions of chemicals in food: (1) food additives which includes ingredients and chemicals indirectly entering food from packaging and processing equipment, and (2) generally recognized as safe (GRAS) substances mostly used as ingredients. The law requires food additives to undergo approval by the U.S. Food and Drug Administration (FDA) before they are sold, but it GRAS substances are exempted from pre-market approval. In 1997, FDA created a voluntary program for manufacturers to submit their chemical's safety determination in the form of a GRAS notice to the agency. Manufacturers make GRAS determinations regardless of whether they voluntarily submit a notice to FDA for review. They rely on their own employees, the employee of a hired consulting firm or a panel of experts, known as GRAS panel, to review the safety information. Because this process determines whether a chemical is safe for use in food, conflicts of interest and biases need to be avoided or minimized to credibly ensure food is safe. Recently, FDA has published guidance for industry on best practices to convene GRAS panels to manage conflicts of interest and reduce biases that have plagued the process. Here, we perform a qualitative assessment of the compliance of GRAS panels with basic elements of FDA's guidance. We assessed 403 GRAS notices filed by FDA between 2015 and 2020 and identified whether a GRAS panel was convened and by whom, its members, affiliations, and relationships between panelists and panel conveners. Then, we compared FDA's recommendations against the information included in the notices voluntarily submitted by manufacturers. We found no evidence that GRAS panels have adhered to FDA's guidance. Panels are populated from a very small pool of professionals; we found that seven panel members alone occupied almost half of all available panel positions and that they often serve together. Against guidance recommendations, ad-hoc panels have been substituted by panels with recurring members in hired consulting firms' payroll. The widespread persistence of conflicts of interest, appearance of conflict and bias in GRAS determinations continue to put the health of Americans at risk and undermine confidence in the safety of food ingredients in the US market. FDA should require notice for all GRAS determinations including how the financial conflicts of interest of those who make these determinations are minimized.